Reducing Runoff Loss of Applied Nutrients in Oil Palm Cultivation Using Controlled-Release Fertilizers - A. Bah; M. H. A. Husni; C. B. S. Teh; M. Y. Rafii; S. R. Syed Omar; O. H. Ahmed (Advances in Agriculture)
Controlled-release fertilizers are expected to minimize nutrient loss from crop fields due to their potential to supply plant-available nutrients in synchrony with crop requirements. The evaluation of the efficiency of these fertilizers in tropical oil palm agroecological conditions is not yet fully explored. In this study, a one-year field trial was conducted to determine the impact of fertilization with water soluble conventional mixture and controlled-release fertilizers on runoff loss of nutrients from an immature oil palm field. Soil and nutrient loss were monitored for one year in 2012/2013 under erosion plots of 16 m2 on 10% slope gradient. Mean sediments concentration in runoff amounted to about 6.41 t ha−1. Conventional mixture fertilizer posed the greatest risk of nutrient loss in runoff following fertilization due to elevated nitrogen (6.97%), potassium (13.37%), and magnesium (14.76%) as percentage of applied nutrients. In contrast, this risk decreased with the application of controlled-release fertilizers, representing 0.75–2.44% N, 3.55–5.09% K, and 4.35–5.43% Mg loss. Meanwhile, nutrient loss via eroded sediments was minimal compared with loss through runoff. This research demonstrates that the addition of controlled-release fertilizers reduced the runoff risks of nutrient loss possibly due to their slow-release properties.